Some aspects of human resources health in Siberian Federal District - E. A. Finchenko; L. S. Shalygina; M. A. Sadovoj; E. V. Mamonova; A. V. Shalygina (Бюллетень сибирской медицины)
Introduction. One of the main national postulates, including domestic health care, is the thesis that the cadres decide everything. At the same time, in recent years, insufficient attention has been paid to human resources for health in scientific research.Materials and methods. An analysis of the data provided by the health authorities of the regions of the Siberian Federal District (SFO) for the preparation of materials for the meeting of the Coordination Council on Health of the Interregional Association “Siberian Agreement”.Results. In general, according to the SFD, the index of the population’s supply of physical persons to physicians is 36,9 per 10 thousand of population, which is somewhat lower than the average Russian indicator (37,2). In general, according to the SFD, the indicator of the population’s availability of doctors for the occupied positions is 56,6 per 10 thousand of the population. In most regions, the part-time ratio exceeds the Russian average (1,4).In general, in the SFD, the provision of the population with doctors in outpatient care is only 17,2% higher than in inpatient care. The staffing level is quite high (90,4%), but to a large extent it was achieved due to a high level of part-time (1,5). The staffing of doctors in outpatient care is 4,7% lower than in inpatient care. At the same time, the higher staffing of physicians in inpatient care is largely due to part-time work (a factor of 1,7 and 1,4 respectively).Staffing by district doctors is quite high and amounts to 93,7% with a very low level of intercourse (1,1). The staffing of the specialists in the SFO is also quite high (89,8%), while it was largely achieved due to the high level of part-time (1,5). The staffing of doctors in outpatient care is 4,7% lower than in inpatient care. At the same time, the higher staffing of physicians in inpatient care is largely due to part-time work (a factor of 1,7 and 1,4 respectively).According to the SFD, the provision of the population with average medical personnel is 124,7 per 10 thousand of the population. The provision of the population with medium-level medical personnel in outpatient and inpatient care is almost the same (56,7 and 56,9 per 10 thousand of the population, respectively). The staffing level of the average medical personnel is quite high (93,7%), to a certain extent, it was achieved through intercourse (1,3). At the same time, the average medical staff in outpatient care is 3,6% lower than in a stationary clinic with practically the same level of part-time (1,2 and 1,3 respectively)The staffing of nurses in the SFO is quite high (94,4%), to a certain extent, it has also been achieved through part-time work (1,3). At the same time, the average medical staff in outpatient-polyclinic care is 3,6% lower than in the stationary one with practically the same level of part-time (1,2 and 1,3 respectively). In general, according to the SFO, there are 2,5 employed nurses for one doctor of clinical specialties. In inpatient care, the number of nurses per doctor is 3,6, and in the outpatient clinic – 1,9.Discussion. It seems more expedient to talk not about the absolute shortage of personnel, but about the relative, which, to a large extent, is caused by disproportions in the placement and use of personnel.Conclusion. By regions, the greatest number of deviations from the mean values for the SFO was revealed by the following parameters: qualification of doctors; Provision by medium-sized medical personnel; Availability of doctors, including medical specialists and staffing of doctors. In staffing in all regions of the SFO, priority is given to inpatient care over outpatient and outpatient care. The adequately high staffing is largely due to the high level of part-time, especially medical specialists. Practically in all regions of the SFD there is not enough high level of qualification of doctors and nurses. In all regions of the SFO, there is a significant shortage of nurses with a sufficiently high level of provision with average medical personnel in general.